Knowledge and practices on family development of 4Ps beneficiaries in Camarines Sur, Philippines - Dy, Stanley O. (The Journal of Public Affairs and Development, 2018)
The study assessed the knowledge and practices on family development among the 4Ps beneficiaries in Camarines Sur. Research methods employed were survey, KIIs, and review of secondary data. The data gathered from the 169 randomly selected respondents were analyzed through descriptive statistics, particularly frequency, percentage, and mean. Most topics discussed during family development sessions relate to disaster risk reduction and management, according to 27% of the respondents. Other topics were on fire, gardening, barangay improvement, community, and nutrition. Almost all respondents indicated that the family development sessions (e.g., proper parenting) are effective, relevant, interesting, and are easy to apply. They added that they teach their children the lessons that they learned from the sessions, and they also expressed willingness to encourage other beneficiaries to do the same. There was high satisfaction level from the respondents; thus, increase in knowledge resulted in positive changes in practices. In terms of proper hygiene among their children, it is important to note that only 46% of the respondents reported that they no longer experience having illnesses. Most respondents indicated that they give high importance to their health and safety. Findings of this research could be useful in planning family development campaigns for behavior change. Future studies may assess other sectors relevant to the agenda using various research designs and measuring other variables of changes in behavior. The 4Ps program should be evaluated to better cater to the needs of its beneficiaries, and its provisions must align with policies relating to parenting, education, and capacity development.